Doping Control Laboratory performance during Rio 2016 Olympic Games: An inside professional overview - Sardela, V. F.; Costa Padilha, M.; Gualberto Pereira, H. M. (Journal of Human Sport & Exercise, 2018)
The paper published in JHSE by Nascimento et al. titled "Laboratory performance: Doping in Olympic sports and Rio 2016 Games" (Nascimento et al., 2018) presents a lack of clarity and enormous inaccuracy about the Brazilian Doping Control Laboratory performance during 2016 Olympics and Paralympics Games of Rio de Janeiro. The authors based their personal opinion on different regulatory reports on the anti-doping control situation in the Olympic Games (OG) in Brazil, but several paragraphs come from the anecdotal and mediatic background. Moreover, classical misinterpretation relative to the anti-doping system from people out of context was presented. The work developed in the Laboratório Brasileiro de Controle de Dopagem (Brazilian Doping Control Laboratory - LBCD-LADETEC/IQ-UFRJ) during the Games represented the state of the art in doping control analysis. In addition, regarding the analytical, infrastructure and security perspectives, the Report by the Independent Observers mentioned: "LBCD made a tremendous effort to ensure it was fully prepared to meet these requirements. As a result, LBCD is an outstanding legacy from the Games for the anti-doping movement in South America" .